Particleboard properties from duabanga moluccana and endospermum diadenum - Jafaruddin, Ali. (Universiti Malaysia Sarawak (UNIMAS), 2005)
The mechanical and chemical properties of the particleboard from Duabanga moluccana and Endospermum diadenum were evaluated. The wood were chopped, flaked, grind and sieved into fine particles for particleboard fabrication and in chemical analysis, sawdust smaller than 40 1.1 were used. The particleboards were fabricated in density of 600 700 and 800 kglmJ using 10 % urea formaldehyde (UF) and I % hardener (NH4CI). Chemical analysis indicated that hot and cold water solubility were 7.03 % and 5.04 % respectively for D. moluccana and 3.37 % and 3.44 %respectively for E. diadenum. It also indicated that D. moluccana have 40.87% lignin and 3.93 % extractives and 39.29 % and 2.76 % for E. diadenum. Particleboard from D. moluccana and E. diadenum showed maximum mechanical properties for different densities. For D. moluccana, maximum properties were 22.68 N/mm2 for Modulus of Rupture (MOR), 2151.80 N/mm2 for Modulus of Elasticity (MOE), 0.87 N/mm2 for Internal Bond Strength (IBS) and 102.59 % for Water Absorption. Maximum properties for E. diadenum were 23.87 kg/mJ for MOR, 2255.64 N/mm2 for MOE, 0.86 N/mm2 for IBS and 78.39 % for Water Absorption. E. diadenum showed best mechanical properties at density of 800 kglmJ. The best mechanical properties for D. moluccana weTe obtained with different density level.